2022
DOI: 10.1002/advs.202201505
|View full text |Cite
|
Sign up to set email alerts
|

Alarming and Calming: Opposing Roles of S100A8/S100A9 Dimers and Tetramers on Monocytes

Abstract: Mechanisms keeping leukocytes distant of local inflammatory processes in a resting state despite systemic release of inflammatory triggers are a pivotal requirement for avoidance of overwhelming inflammation but are ill defined. Dimers of the alarmin S100A8/S100A9 activate Toll‐like receptor‐4 (TLR4) but extracellular calcium concentrations induce S100A8/S100A9‐tetramers preventing TLR4‐binding and limiting their inflammatory activity. So far, only antimicrobial functions of released S100A8/S100A9‐tetramers (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The tetramer is able to bind CD69 on monocytes and act in an immunoregulatory manner. Signalling via CD69 has a calming effect on monocytes and dampens inflammatory responses in disease models [ 22 ]. CD69 expression is low on neutrophils [ 40 ] but constitutively expressed on platelets [ 41 ], and appears as a likely candidate to transduce a calming effect of tetrameric S100A8/A9 to reduce PNC formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetramer is able to bind CD69 on monocytes and act in an immunoregulatory manner. Signalling via CD69 has a calming effect on monocytes and dampens inflammatory responses in disease models [ 22 ]. CD69 expression is low on neutrophils [ 40 ] but constitutively expressed on platelets [ 41 ], and appears as a likely candidate to transduce a calming effect of tetrameric S100A8/A9 to reduce PNC formation.…”
Section: Discussionmentioning
confidence: 99%
“…Tetramerisation hides the TLR4-binding site in the tetramer interphase, and mutations in the heterodimer that inhibit tetramerisation lead to an uncontrolled activity. Current work demonstrates the inhibitory, calming effect of S100A8/A9 tetramer on monocytes mediated by the receptor CD69 [ 22 ]. Platelets also express CD69, yet the effect of the S100A8/A9 tetramer on platelets and PNC formation is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our new data support recent findings of a new extracellular function of S100A8/S100A9 on murine monocytes, whereby missing extracellular S100A8/S100A9 causes the preactivation of these cells. This effect is not linked to proinflammatory S100A8/S100A9 dimers, and is exclusively restricted to calcium-induced tetramers of S100A8/S100A9 binding and activating CD69 on monocytes [ 58 ]. We also recently showed that the contact of neutrophils with the endothelium leads to a rapid S100A8/S100A9-dimer release, and that these dimers in turn bind in an autocrine manner to the neutrophil’s Toll-like receptor 4 and initiate the activation of β2-integrins from a low-affinity to an intermediate-affinity state.…”
Section: Discussionmentioning
confidence: 99%
“…Direct binding experiments have shown that the S100A8/A9 tetramer, but not the dimer, binds to CD69. The regulatory function of the tetramer could be demonstrated in vitro as well as in vivo in models of cutaneous granuloma and irritant contact dermatitis ( 30 ). A direct effect of S100-dimers on CD69 is now excluded by our study.…”
Section: Discussionmentioning
confidence: 99%
“…CD69 is known for its involvement in the differentiation of regulatory T cells via the Jak3/Stat5 signaling pathway ( 28 ). Gal-1 has been identified as a specific ligand for CD69, but the S100A8/S100A9 complex is also a putative ligand that was found to influence T cell differentiation as well as the regulation of cytokines such as IL-17A and TGF-ß ( 18 , 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%